2017
DOI: 10.2147/ijn.s125573
|View full text |Cite
|
Sign up to set email alerts
|

Cyclic RGD peptide-modified liposomal drug delivery system for targeted oral apatinib administration: enhanced cellular uptake and improved therapeutic effects

Abstract: Apatinib is an oral tyrosine kinase inhibitor, which selectively targets vascular endothelial growth factor receptor 2 and has the potential to treat many tumors therapeutically. Cyclic arginylglycylaspartic acid (cRGD)- and polyethylene glycol (PEG)-modified liposomes (cRGD-Lipo-PEG) were constructed to act as a targeted delivery system for the delivery of apatinib to the human colonic cancer cell line, HCT116. These cRGD-modified liposomes specifically recognized integrin α v β … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
46
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 86 publications
(50 citation statements)
references
References 43 publications
2
46
0
Order By: Relevance
“…In another study, apatinib-loaded liposomes were surface modified with targeting ligand, cyclic arginylglycylaspartic acid (cRGD), to specifically recognize αvβ3 integrin. 104 These cRGDanchored liposomes, compared with nontargeted liposomes, showed improved cellular uptake and inhibition of tumor growth in human colon HCT116 cancer cell line. Similarly, Wu et al 105 investigated the effect of folate targeting on the antitumor efficacy of paclitaxel-encapsulated PMs in human esophageal cancer cell lines, EC9706.…”
mentioning
confidence: 95%
“…In another study, apatinib-loaded liposomes were surface modified with targeting ligand, cyclic arginylglycylaspartic acid (cRGD), to specifically recognize αvβ3 integrin. 104 These cRGDanchored liposomes, compared with nontargeted liposomes, showed improved cellular uptake and inhibition of tumor growth in human colon HCT116 cancer cell line. Similarly, Wu et al 105 investigated the effect of folate targeting on the antitumor efficacy of paclitaxel-encapsulated PMs in human esophageal cancer cell lines, EC9706.…”
mentioning
confidence: 95%
“…2,7 The insertion of ligand molecules having specificity to tumorspecific surface receptors or endothelial cells directly into neovascular vessels of a tumor is regarded as effective approach providing cancer cell specificity to nanocarriers. [8][9][10][11] To control drug release profiles, external stimuli-sensitive properties such as temperature, pH, magnetic field and light have been applied for nanocarriers. [12][13][14][15][16][17][18][19][20][21] ThermoDox is one example of a temperature-responsive liposome designed to achieve drug release at tumor tissues under local heating of tumor tissues.…”
Section: Introductionmentioning
confidence: 99%
“…Enhancement of cellular uptake of drugs by actively-targeted nanoparticles is widely supported by the literature. Song et al [20] showed that cellular uptake of liposomal apatinib was enhanced by the conjugation of cyclic-RGD to the liposomal DD system. An 11.2-fold increase in cellular uptake was achieved by the modification of a liposomal doxorubicin system with an SP5-2 moiety by Chang et al [21] Transferrinmodified nanoparticles demonstrated a six-fold increase in uptake versus control liposomes for a breast cancer cell line [22].…”
Section: Structure Of Nanocarriersmentioning
confidence: 99%